Avaliação de propriedades físicas e mecânicas de compósitos verde de espuma rígida de pu de óleo vegetal com serragem de Pinus taeda e fibras de Agave sisalana - Paula, Caroline Rodrigues Pereira de (2024)
Polymeric materials made from petroleum can have a negative impact on the environment and health due to their non-renewable origin and the presence of harmful solvents. On the other hand, polyurethane foam derived from vegetable oils is biodegradable, comes from renewable sources and is free of solvents that are harmful to health. Pinus taeda sawdust, one of the main waste products from the timber sector, and sisal fiber from the Agave sisalana plant, grown in Brazil, are materials that can be used to make composites. The aim of this work was to physically and mechanically analyze rigid foam composites with Pinus taeda sawdust and Agave sisalana fibers, produced with different production parameters, based on the study carried out by Paula (2017). Based on the results obtained from the analysis of the rigid foam pressing parameters, the manufacturing parameters of 16 different combinations of composites produced with rigid foam, sawdust and sisal were evaluated. The rigid foam and composites were characterized by density, SEM micrographs and flexural strength. The composite with the highest flexural strength was reproduced and evaluated by density analysis, water absorption and swelling in thickness, acoustic absorption, thermogravimetric analysis, flexural strength after UVA irradiation, flammability and perforation. All data was statistically analyzed. No similar analyses of foam pressing parameters were found in the literature with the same approach as in this work. Rigid polyurethane foams derived from vegetable oils produced under a pressure of 4 MPa for 20 minutes at room temperature had an average density of 249 kg/m³ and a maximum flexural stress of 3.07MPa. Composites with 50% rigid foam, 45% sawdust and 5% sisal pressed at 25ºC for 20 minutes had an average density of 767 kg/m³ and a flexural stress resistance of 19.76MPa, values higher than those found by Paula (2017), suggesting that the packing and covering of the fibers were adequate, favoring the transmission of stresses. In addition, these composites were resistant to swelling caused by water and are suitable for structural and non-structural use.